Strain mapping using electron backscatter diffraction - Wilkinson, A; Dingley, D; Meaden, G (Springer US, 2009)
In this chapter we review the progress that has been made toward elastic strain (i.e., stress) mapping using electron backscatter diffraction. In particular we focus on development of an analysis method based on using cross-correlation to determine small shifts in the EBSD patterns with respect to a reference pattern. The pattern shifts are determined at many subregions dispersed across the wide angular span of the EBSD pattern, and the magnitude and angular distribution of shifts allows the strain and rotation tensor to be determined. Pattern shifts at a resolution of ±0.05 pixels, or in some cases even better, have been reported, which corresponds to a sensitivity of ∼±10-4 in the components of the strain and rotation tensor. © Springer Science+Business Media, LLC 2009. All rights reserved.